Integration of Multi Intelligence in Quality of Innovation in Public Services through the Spiritual Intelligence - Noor, Irwan; Ambulani, Nur (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2024)
This research examines the integration of spiritual intelligence in public administration and its impact on service innovation. Conducted in Malang City, East Java, the study employed a survey method targeting residents aged 18 years and above who have utilized public services from the local government. A stratified sampling method was utilized to select a sample of 355 individuals. The independent variables investigated encompass social intelligence, cultural intelligence, emotional intelligence, and intellectual intelligence, while service innovation serves as the dependent variable, with spiritual intelligence acting as a moderating variable. Data were gathered through closed questionnaires, subsequently validated and assessed for reliability using the Karl Pearson method and the Cronbach Alpha test. Subsequent data analysis was performed employing SPSS to ascertain validity and reliability, and Smart-PLS for further analysis. This research aims to scrutinize the relationship between spiritual intelligence and service innovation within the realm of public administration, aiming to contribute novel insights into the integration of spiritual intelligence in the advancement of more comprehensive and efficacious public services. The findings underscore that the integration of spiritual intelligence in public administration exerts a positive influence on service innovation, underscoring the significance of incorporating the spiritual dimension in the development of inclusive public services.